Effect of transverse and longitudinal magnetic field on the excess conductivity of YBa₂Cu₃₋zAlzO₇₋δ single crystals with a given topology of plane defects - Vovk, R.V.; Nazyrov, Z.F.; Khadzhai, G.Ya.; Pinto Simoes, V.M.; Kruglyak, V.V. (Functional Materials, 2013)
The effect of a constant magnetic field to 12.7 kOe on the temperature dependences of electric conductivity of aluminum-doped YBaCuO single crystals with a system of unidirectional twinning boundaries has been investigated. It is determined that the twinning boundaries are effective centers of scattering of fluctuation carriers. Directly near Tc the temperature dependences of the excess paraconductivity are satisfactorily described by the Hikami-Larkin theoretical model of fluctuation conductivity for layered superconducting systems. The reasons for the suppression of three-dimensional superconducting fluctuations and the nonmonotonic dependence of ξc(0,H) in weak magnetic fields with the magnetic field vector oriented along c axis were discussed. It was shown that the lack of fan-shaped expansion of the resistive transitions in the magnetic field in these samples is conditioned by the lack of the no pinning vortex liquid phase due to increased pinning of the vortex lattice at the twin boundaries.